The Belt and Road Initiative: Implications for Economic Development in Africa - ‘Mokose, ‘Manapo (Department of Political Studies, 2021)
This study examines the possible impact of the Belt and Road Initiative (BRI) on economic development in Africa. Launched in October of 2013, the initiative was established to alleviate trade and investment bottlenecks between the more than 65 countries that are signed on to it as member states. In 2017, it became the centrepiece of China's foreign economic policy and the filter through which all of its commercial ties with external actors would be pursued, framed, or determined. It is expected that when fully operationalized, the initiative will restructure China's ties with other countries. The study analyses the possible repercussions of that restructuring, focusing on its relationship with Africa. Since consolidating their commercial relationship in the early 1990s, China has played a vital role in developing Africa's economy. With the operationalisation of the BRI, its capacity or interest to maintain that role will be modified. Depending on the changes that emerge, and given its deep economic reliance on Beijing, Africa must prepare for both positive and negative implications for its economies. The study examines these implications. It notes, among others, the upgrades Africa stands to gain to its industrial structure and business environment. It also highlights potential losses, including the hit that Africa's revenue earnings might take and the heightened competition that local industries will be exposed to because of the liberalisation that the BRI pursues. Ultimately, the study advises that what outcomes arise – be they positive or negative – will depend on how well or sufficiently the continent positions itself to moderate the negative impact of the BRI on its economies. In the concluding chapter, the study makes recommendations on how Africa might facilitate or magnify projected benefits stemming from the BRI.